A bifunctional 3D porous Zn-MOF: Fluorescence recognition of Fe3+ and adsorption of congo red/methyl orange dyes in aqueous medium. (January 2022) - Gao, Lingling; Gao, Ting; Zhang, Yujuan; Hu, Tuoping
Abstract: Fe 3+ Herein, a bifunctional 3D porous metal-organic framework (Zn-MOF) was synthesized based on the solvothermal reaction of tri(p-carboxyphenyl)phosphane oxide (H3 L) and Zn salts, and characterized by powder X-ray diffraction (PXRD), thermogravimetric (TG), Infrared (IR), X-ray photoelectron spectroscopy (XPS) and Brunauer-Emmett-Teller (BET). The results show that Zn-MOF has high stability and its specific surface area and pore size are 102.36 m 2 g −1 and 2.94 nm, respectively. Meanwhile, Zn-MOF exhibited excellent adsorption performance for Congo red (CR) and Methyl orange (MO) dyes. The adsorption of CR dyes by Zn-MOF is mainly due to the sedimentation caused by gravity of large molecules formed by hydrogen bonding between –NH2 in CR dye molecules and μ 3 -OH - in Zn-MOF, while the adsorption of MO by Zn-MOF is mainly attributed to that the larger pore size of Zn-MOF is conducive to MO dye molecules into the channels of Zn-MOF. At the same time, a series of fluorescence experiments showed that Zn-MOF can also sensitively recognize Fe 3+ ion in aqueous medium with the limit of detection of 0.09716 μM, which is inferior to the previously reported values. Furthermore, the recognition mechanism of Zn-MOF for Fe 3+ ion is mainly ascribed to the internal filtering effect (IFE) by the characterization of PXRD, UV–vis and fluorescence lifetime. Graphical abstract: Image 1 Highlights: A three-dimensional (3D) porous Zn-based metal-organic framework (Zn-MOF) was synthesized under solvothermal conditions. Zn-MOF can adsorb congo red/methyl orange dyes in aqueous medium. Zn-MOF can recognize Fe 3+ ions in water with the limit of detection value of 0.09716 μM.